Restorative Justice and Anti-LGBT Hate Crimes: Experiences and Disparities from the Ground - Ignacio Elpidio Domínguez Ruiz; Malin Roiha (Droit et Cultures)
Restorative justice is a complex, debated paradigm often defined as an approach to social justice that prioritizes restoration. It is particularly relevant for addressing anti-LGBT hate crimes and discrimination due to its potential to reduce secondary victimization, improve victim wellbeing, and generate social transformations. Drawing from qualitative interviews with LGBT NGO and justice professionals from six European Union member states, we analyze their experiences with restorative justice in cases of LGBT hate crimes to delineate its practical parameters, as well as its potentialities and limitations, and we identify significant conceptual and experiential dissonances and gaps. We argue that restorative justice processes can be productively designed and adapted, but the existing practices and expectations of our research participants do not always conform to restorative paradigms that achieve these goals, which points to the need for a shift in justice culture and training to implement restorative practices.